2020
DOI: 10.7150/jca.46429
|View full text |Cite
|
Sign up to set email alerts
|

VEGF promotes migration and invasion by regulating EMT and MMPs in nasopharyngeal carcinoma

Abstract: Background: Vascular endothelial growth factor (VEGF) is an important pro-angiogenic factor. Accumulating data have indicated that VEGF is involved in tumour metastasis. However, the mechanism through which VEGF regulates nasopharyngeal carcinoma (NPC) metastasis is largely unknown. This study aimed to examine the biological function of VEGF in NPC metastasis and its underlying mechanism. Methods: We used western blotting and qPCR to examine the difference in VEGF expression between NPC cells and the immortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 57 publications
1
31
0
Order By: Relevance
“…These data suggest that for nasopharyngeal carcinoma, CRYAB-dependent VEGFA expression participates in regulating EMT inhibition in LBH-elevated NPC cells induced by exosome-mediated autocrine signaling, which attenuates cellular migration and invasion. This is consistent with the views of Chen et al [46] and Schootbrugge et al [47] that both VEGFA and CRYAB promote EMT progression and metastasis in head and neck carcinoma. The exact role of VEGFA in modulating metastasis-associated phenotypes of NPC cells affected by exosome-mediated autocrine signaling, however, requires further verification by introducing VEGFA interference during exosome treatment, for example, with receptor inhibitors, neutralizing antibodies or recombinant proteins.…”
Section: Discussionsupporting
confidence: 92%
“…These data suggest that for nasopharyngeal carcinoma, CRYAB-dependent VEGFA expression participates in regulating EMT inhibition in LBH-elevated NPC cells induced by exosome-mediated autocrine signaling, which attenuates cellular migration and invasion. This is consistent with the views of Chen et al [46] and Schootbrugge et al [47] that both VEGFA and CRYAB promote EMT progression and metastasis in head and neck carcinoma. The exact role of VEGFA in modulating metastasis-associated phenotypes of NPC cells affected by exosome-mediated autocrine signaling, however, requires further verification by introducing VEGFA interference during exosome treatment, for example, with receptor inhibitors, neutralizing antibodies or recombinant proteins.…”
Section: Discussionsupporting
confidence: 92%
“…The expression of vimentin and N-cadherin are thought to facilitate the progress of cell invasion, migration, and EMT process [ 43 ]. It was reported that several genes, including vascular endothelial growth factor [ 44 ] and forkhead box 1 [ 45 ], modulated NPC migration and invasion by regulating the EMT. In this study, overexpression of RPL14(eL14) notably repressed cell migration, invasion, and EMT process in NPC cells by reducing the expression of N-cadherin and vimentin and increasing the expression of E-cadherin.…”
Section: Discussionmentioning
confidence: 99%
“…Deoxycholic acid appears to be a strong stimulant of the vascular endothelial growth factor (VEGF) expression, 56 which is demonstrated to be a vital pro–angiogenic factor involved in tumor metastasis and angiogenesis. 57 Studies have shown that abnormal secretion of VEGF binds to receptor tyrosine kinases to induce receptor dimerization and phosphorylation, particularly VEGFR1/2, resulting in the process of endothelial regeneration, angiogenesis, and induction of tumor EMT. 58 , 59 Current studies mainly focus on the relationship between VEGFR2 signaling and tumor angiogenesis, and the important role of VEGFR2 in VM formation has been neglected.…”
Section: Discussionmentioning
confidence: 99%